Predição de sintomas comportamentais em crianças e adolescentes submetidos à mudanças climáticas extremas - Ana Paula Oliveira Rodrigues Gandra (2020)
Introduction: The most frequent and important natural disasters throughout the world are floods and droughts. Evidence reveals a significant percentage of children and adolescents directly exposed to disasters and who exhibit reactions to stress, which can interfere with functioning and contribute to disorders in this population. Objectives: To analyze the trajectory of internalizing and externalizing symptoms in children and adolescents exposed to extreme climatic conditions. Methods: 79 participants aged 6 to 18 years exposed to flood and drought conditions were assessed for their behavioral trajectories in two timepoints: at the immediate aftermath of the flood/drought and fifteen months apart from the first evaluation. Results: The groups were similar in terms of education, socioeconomic status and gender distribution. Post-traumatic stress scores were equivalent between groups in the assessment at time 1 (in the experience of the incident). The children in the flood group were younger and showed a significant improvement in internalizing problems over time. In the second moment of evaluation (approximately 15 months after the event), there was stability of the posttraumatic stress score (p> 0.999), internalizing symptoms (p = 0.092) and externalizing symptoms (X2 (1, N = 79) = 2.76, p = 0.251). About the subgroups, the only difference that reached significance (p <0.05) in the proportion of individuals was found in the internalizing symptoms, with children from the drought condition showing a higher frequency of worsening of the symptoms over time when compared to children from the flood condition. Conclusion: Climatic events over time seem to promote impacts on the mental health of children and adolescents in a comparable and even similar way, however the drought event due to its own characteristic of chronicity seems to result in increasing symptomatology of internalizing symptoms.